Modelo de análise de eficiência multidimensional para gestão hospitalar - Soares, Adeilson Barbosa (2017)
The Multidimensional efficiency analysis can provide important insights into the hospitals performance. This thesis proposes a multidimensional model based on Data Envelopment Analysis (DEA) to investigate and compare the efficiency of public hospitals in Brazil. The Data from 21 public hospitals were collected from public databases (OECD - Organization for Economic Co-operation and Development; SIH-SUS - SUS Hospital Information System, Datasus, Brazil). Four inputs (Number of medical and non-medical staff, Annual revenue, Number of beds, Average length of patient hospitalization), four Variables of Influence (Type of hospital, Accredited hospital, Number of medical specialties, Resources from government) and four Outputs (Number of outpatient care services, Number of hospitalizations, Number of surgeries, Number of exams) were used to feed the DEA model. Results show that, Seven hospital units reach 100% efficiency and, according to DEA, can be considered efficient units. Two units were considered “almost efficient” and the remaining twelve units perform poorly, considering the data supplied to the DEA model. As a whole, the average efficiency of the hospitals investigated was 79% (0.79). A very heterogeneous performance has been found among the Brazilian public hospitals investigated. Besides, the reasonably low average efficiency seems to indicate that the system has a large potential for improvement in almost all areas associated with the input and output variables investigated in this paper.